Book Reviews (The Muslim world, 1972)
Book Review in this Articles L'influence du stolcisme sur la pensée musulmane. By Fehmi Jadaane Logic in Classical Islamic Culture. Edited by G. E. von Grunebaum. The Mysticism of Hamzah Fansūri. By Syed Muhammed Naguib al-Attss. Compendium of Fatimid Law. By Asaf A. A. Fyzee. L'HistoIre du Maghrab. By Abdallah Laroui. Ninety-Nine Names of God. By Robert Stade. Lumiére et Ombre su Maghreb. By A. Demeerseman. Alive to God. Muslim and Christian Prayer. Compiled with an Introductory Essay by Kenneth Cragg. I Was an Algerlan Freacher. Autoboigraphy of Said Aboundaon, a Kabyle Pastor. Translated and edited with a prologne, an epilogue and a survay article by W. N. Heggoy. Christ and crisIs in Southeast AsIa. Edited by Gerald H. Anderson.